Implementation of the Tahfizh Al-Qur’an Program in Shaping the Spiritual Intelligence of Student at MBS Zam-Zam Junior High School, Banyumas - Hasan, Muhamad; Sriyanto, Sriyanto; Darodjat, Darodjat; Yani, Achmad (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This study on the implementation of the Tahfizh Al-Qur’an program in enhancing spiritual intelligence was conducted to obtain insights into how this program is applied at Muhammadiyah Boarding School (MBS) Zam-Zam Banyumas Junior High School to foster the spiritual intelligence of its students. The aim of the research is to describe the implementation of the Tahfizh Al-Qur’an program in enhancing the spiritual intelligence of students at MBS Zam-Zam Banyumas Junior High School, focusing specifically on the program’s concept, implementation, and impact. This study uses a qualitative descriptive approach with field research methods. Data analysis was conducted through observation, interviews, and documentation. The findings indicate that the Tahfizh Al-Qur’an program positively impacts students’ spiritual development at MBS Zam-Zam Banyuma Junior High School, evidenced by their respectful speech and conduct, care for others and the environment, and performing acts of worship independently. Thus, memorizing the Qur’an strengthens students' spirituality, faith, and piety toward Allah Swt., as reflected in their daily behavior.